Review Studi Perbandingan Audit Syariah dan Konvensional di Indonesia - Lubis, Rusdi Hamka (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2023)
This research aims to review and compare studies on Shariah and conventional auditing conducted in Indonesia. Through a literature review analysis of three Shariah auditing journal articles and three conventional auditing journal articles, this research identifies the development, challenges, and implementation of information technology in both types of auditing. The findings show that Shariah auditing in Indonesia has progressed well, but requires further in-depth understanding of practical obstacles. Meanwhile, conventional auditing continues to be a choice for non-Shariah companies to achieve financial transparency. This research provides valuable insights and recommendations for further studies to enhance the quality of auditing practices in Indonesia.